2014
DOI: 10.1111/j.1532-950x.2014.12097.x
|View full text |Cite
|
Sign up to set email alerts
|

The Advanced Locking Plate System (ALPS): A Retrospective Evaluation in 71 Small Animal Patients

Abstract: ALPS offers a reliable alternative for fracture treatment and some other orthopedic conditions in small animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
3
24
2
Order By: Relevance
“…Overall complications were encountered in 17% of the fractures and implant-related complications were reported in nine percent of the fractures. These results are similar to those reported in previous studies in which various locking plate systems were used for appendicular fractures repair in small animals (6,(9)(10)(11)(12). The reported overall complication and fixation failure rates were of 19.7% and 10.6% respectively with ComPact Unilock plates, 12.8% and 10.6% respectively with LCP, 11% and eight percent respectively with Fixin locking plates, and 22.5% and 20.9% with the PAX system (6,(9)(10)(11).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall complications were encountered in 17% of the fractures and implant-related complications were reported in nine percent of the fractures. These results are similar to those reported in previous studies in which various locking plate systems were used for appendicular fractures repair in small animals (6,(9)(10)(11)(12). The reported overall complication and fixation failure rates were of 19.7% and 10.6% respectively with ComPact Unilock plates, 12.8% and 10.6% respectively with LCP, 11% and eight percent respectively with Fixin locking plates, and 22.5% and 20.9% with the PAX system (6,(9)(10)(11).…”
Section: Discussionsupporting
confidence: 91%
“…The reported overall complication and fixation failure rates were of 19.7% and 10.6% respectively with ComPact Unilock plates, 12.8% and 10.6% respectively with LCP, 11% and eight percent respectively with Fixin locking plates, and 22.5% and 20.9% with the PAX system (6,(9)(10)(11). Recently clinical experience in fracture repair in small animals using ALPS system, with a fixation failure rate of seven percent has been reported (12).…”
Section: Discussionmentioning
confidence: 99%
“…Locking plates prohibit movement at the plate‐screw interface, which decreases the risk of screw loosening and pull out . Locking plates may offer advantages in thin bones with minimal screw purchase in the bone such as feline ilial fractures …”
mentioning
confidence: 99%
“…[10][11][12][13] Locking plates may offer advantages in thin bones with minimal screw purchase in the bone such as feline ilial fractures. 10,11,[13][14][15][16] The objective of this study was to assess the frequency of implant-associated complications and the extent of pelvic canal narrowing associated with the fixation of ilial fractures in cats with dynamic compression plates (DCP), a single locking plate (LPS), and double locking plates (dLPS) applied on the lateral surface of the ilium. We hypothesized that the frequency of screw loosening would be lower in the fractures fixed with LPS or dLPS compared to fractures fixed with DCP.…”
mentioning
confidence: 99%
“…More recently, the use of locking plates in the stabilisation of periarticular fractures has gained popularity in the treatment of these fractures in humans . Locking plates utilise a variety of different locking mechanisms to create angle‐stable constructs, whereby the screw head engages with the plate screw hole, and have been reported in the veterinary literature for successful stabilisation of many different fractures and osteotomies . The number of screws required in each fragment is still not clearly defined; however, it has been suggested that adequate stability can be achieved with a minimum of two locking screws per fragment, which may prove advantageous when stabilising small bone fragments.…”
mentioning
confidence: 99%